The Effect Of Photography Media On Students’ Writing Ability In Hortatory Exposition Text At Grade Eleven Of SMK GKPI 1 Pematang Siantar - Mely Christi Sihotang; Mungkap Mangapul Siahaan; Melda Veby Ristella Munthe (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The objective of this research was to find out the effect of photography media to writing ability on hortatory exposition text at eleven grade students of SMK GKPI 1 Pematang Siantar. This research focuses on the students’ writing ability in hortatory exposition text using photography media. This research used quantitative research with a quasi-experimental research design. The population of this study was the eleven grade students of SMK GKPI 1 Pematang Siantar with a total of 159 students. The sample of this study was divided into two classes, namely the experimental class (XI Kewirausahaan) consisting of 25 students who used photography media and the control class (XI TKJ) consisting of 25 students who used conventional media. Data collection instruments used writing tests for pre-test and post-test. Jacob et. al's writing assessment rubric was used in this research, which includes several aspects: content, organization, vocabulary, language use, and mechanics. The result of this research showed that at the 5% significance level (a=0.05), t-test was higher than t-table in which t-test= 3,514>t-table= 1,677. As a result, HO is rejected while Ha is accepted. Therefore, it can be concluded that photography media significantly affects the ability of students at SMK GKPI 1 Pematang Siantar in writing hortatory exposition text.